A key performance indicators redefinition initiative at a school of pharmacy using a modified Delphi consensus technique - Teresa M. Salgado; Taylor N. Reynolds; Laura M. Frankart; David A. Holdford; Joseph T. DiPiro (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Objective: The Outcomes and Assessment Committee at the Virginia Commonwealth University School of Pharmacy was tasked with refining the school's key performance indicators (KPIs) to improve programmatic assessment by focusing on the most important measures. Methods: Initially, 56 KPIs were tracked, nine of which were university mandated, divided into 10 modules: admissions, community outreach, continuing education, diversity, faculty experience and success, fundraising, graduate program, research and scholarship, staff experience and success, and student experience and success. Using a three-round Delphi consensus technique, KPIs were reviewed by faculty and staff. Each participant responded whether they considered each KPI to be essential or not essential for school quality assessment and improvement. Consensus for the first, second, and third rounds was defined as ≥90%, ≥80%, and ≥75% agreement, respectively. Results: Of 109 faculty and staff invited, 49 participated in the first round, 51 in the second, and 42 in the third. At the end of the third round, accumulated consensus was achieved for 35 out of 88 (39.8%) KPIs that were considered essential and 3 out of 88 (3.4%) that were considered non-essential. Consensus percentage per module was: 15.4% (2/13) admissions, 28.6% (2/7) community outreach, 33.3% (3/9) continuing education, 27.3% (3/11) diversity, 62.5% (5/8) faculty experience and success, 55.6% (5/9) fundraising, 40% (4/10) graduate program, 33.3% (3/9) research and scholarship, 57.1% (4/7) staff experience and success, and 66.7% (4/6) student experience and success. Conclusions: Ultimately, 35 KPIs achieved consensus as essential to measure achievement of benchmarks for the school, which totals 44 KPIs, including nine university mandated KPIs. The process facilitated faculty and staff involvement in KPI selection and achieved improved focus for programmatic assessment.